Improved High Temperature Thermoelectric Properties in Misfit Ca3Co4O9 by Thermal Annealing - Arindom Chatterjee; Alexandros El Sachat; Ananya Banik; Kanishka Biswas; Alejandro Castro-Alvarez; Clivia M. Sotomayor Torres; José Santiso; Emigdio Chávez-Ángel (Energies, 2023)
Ca3Co4O9, a p-type thermoelectric material based on transition-metal oxides, has garnered significant interest due to its potential in thermoelectric applications. Its unique misfit-layered crystal structure contributes to low thermal conductivity and a high Seebeck coefficient, leading to a thermoelectric figure of merit (zT) of ≥1 at 1000 K. Conventionally, it has been believed that thermopower reaches its upper limit above 200 K. However, our thermopower measurements on polycrystalline Ca3Co4O9 samples have revealed an unexpected increase in thermopower above 380 K. In this study, we investigate the effects of high oxygen pressure annealing on Ca3Co4O9 and provide an explanation based on the mixed oxide states of cobalt and carrier hopping. Our results demonstrate that annealing induces modifications in the defect chemistry of Ca3Co4O9, leading to a decrease in electron hopping probability and the emergence of a thermal activation-like behavior in thermopower. These findings carry significant implications for the design and optimization of thermoelectric materials based on misfit cobaltates, opening new avenues for enhanced thermoelectric performance.